2015
DOI: 10.1097/olq.0000000000000353
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing, HIV Positivity, and Linkage and Referral Services in Correctional Facilities in the United States, 2009–2013

Abstract: Background Because of health disparities, incarcerated persons are at higher risk for multiple health issues, including HIV. Correctional facilities have an opportunity to provide HIV services to an underserved population. This article describes Centers for Disease Control and Prevention (CDC)–funded HIV testing and service delivery in correctional facilities. Methods Data on HIV testing and service delivery were submitted to CDC by 61 health department jurisdictions in 2013. HIV testing, HIV positivity, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…The significant association between being in jail and being offered PN might be a consequence of expanding HIV testing and linkage in correctional facilities, developed in response to high rates of HIV among criminal justice involved populations. 23,24 This finding is consistent with a national study demonstrating that over half of newly diagnosed black men in jail and prison were referred to PN. 23 Yet our results also show that HIV diagnosed individuals who were previously jailed were no more likely to provide partner names when offered PN than those who were not jailed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The significant association between being in jail and being offered PN might be a consequence of expanding HIV testing and linkage in correctional facilities, developed in response to high rates of HIV among criminal justice involved populations. 23,24 This finding is consistent with a national study demonstrating that over half of newly diagnosed black men in jail and prison were referred to PN. 23 Yet our results also show that HIV diagnosed individuals who were previously jailed were no more likely to provide partner names when offered PN than those who were not jailed.…”
Section: Discussionsupporting
confidence: 89%
“…23,24 This finding is consistent with a national study demonstrating that over half of newly diagnosed black men in jail and prison were referred to PN. 23 Yet our results also show that HIV diagnosed individuals who were previously jailed were no more likely to provide partner names when offered PN than those who were not jailed. There are many barriers to improving the HIV care continuum in correctional facilities including HIV stigma, fear of status disclosure and ensuing discrimination, retribution, and danger to personal safety.…”
Section: Discussionsupporting
confidence: 89%
“…134,135 While there is no evidence that minorities experience higher rates of mental health issues, there are disparities in mental health care. 136 These disparities may contribute to why African-American and Hispanic MSM are disproportionately affected by these structural barriers associated with HIV, consistent with longstanding social and economic inequity.…”
Section: Mental Health and Hiv Prevention Engagement And Carementioning
confidence: 99%
“…The care provided to people with HIV/AIDS in prison was addressed by the articles regarding the following themes: HIV prevention,12,19 HIV testing and diagnosis,13-16 HIV treatment, [13][14][15][16] Articulation with health services in addressing HIV. 12,15,18,20 In the HIV prevention theme, it was found that the development of such action within the PU can be an alternative to decrease the number of new cases of detainees infected with the virus, 19 however there are prisons that represent a high-risk environment for the HIV transmission. Another study points to the low referral of detainees to health services for the provision of HIV prevention actions, with emphasis on testing and test results, medical consultation after diagnosis of the virus infection and guidelines on exposure of the virus to partner.…”
Section: Resultsmentioning
confidence: 99%
“…Another study points to the low referral of detainees to health services for the provision of HIV prevention actions, with emphasis on testing and test results, medical consultation after diagnosis of the virus infection and guidelines on exposure of the virus to partner. 12,19 In relation to testing and counseling, a study conducted in Italy in 2013 found that all PUs studied offered HIV testing. 13 Another study conducted in Malaysia found that 66.9% of participants were diagnosed with HIV in a previous incarceration, 56.5% in the current incarceration and 10.5% by compulsory testing during incarceration.…”
Section: Resultsmentioning
confidence: 99%